When ‘research ethics’ become ‘everyday ethics’: the intersection of inquiry and practice in practitioner research - Mockler, Nicole (Educational Action Research, 2014)
The act of engaging in sound and ethical practitioner research, regardless of context, encourages and indeed demands an alignment between the ethical framework employed in the research enterprise and the ‘everyday ethics’ of practice. This paper explores the ethical dimensions of what Cochran-Smith and Lytle (2007a, 2009) have termed ‘the dialectic’ of practitioner inquiry: “the reciprocal, recursive, and symbiotic relationships of research and practice, analysis and action, inquiry and experience, theorizing and doing, and being researchers and practitioners” (2007a, p. 31). It argues that the reflexive nature of the theory/practice dynamic means that in the context of sustained practitioner inquiry, the ethics of research and the ethics of practice both hold the potential to be shaped by and to shape the other. Elsewhere in discussions of the issue of quality in practitioner and other practice-based research, (2006, 2007, 2009), GroundwaterSmith and Mockler have argued that ethical professionalism can and does work as a platform for quality, pushing practitioner inquiry ‘beyond celebration’. This paper builds on these ideas, and in exploring the intersection of inquiry and practice in practitioner research, examines the implications of issues relating to: informed consent; ‘voice’ and ownership; transparency and negotiation; confidentiality, anonymity and trust; and deliberative action in the context of both practitioner inquiry and classroom practice.